A Tawhid Analysis Of Worshiping Created Beings In Shaykh Ibn Baz's View - Avanticha Dewi Harits; Mutia Azra Khadijah; Agung Pranoto Kadiatmaja (AL - IBRAH, 2025)
This paper examines the concept of tawhid as the fundamental principle in understanding the prohibition against worshipping created beings, based on the perspective of Shaykh Ibn Baz. The study aims to explain how tawhid al-uluhiyyah (the oneness of divinity in worship) confines all forms of devotion exclusively to Allah while rejecting any form of veneration directed toward prophets, angels, saints, or other creatures. Employing a qualitative, library-based research design through a content analysis approach, this study investigates selected Qur’anic verses, authentic hadiths, and the writings of Shaykh Ibn Baz to identify the patterns of reasoning and theological foundations underlying his thought. The analysis reveals that Ibn Baz consistently emphasizes tawhid al-uluhiyyah as the primary safeguard against various forms of contemporary polytheism, including the deification of individuals and the redirection of supplications to entities other than Allah. The findings indicate that approximately seventy percent of Ibn Baz’s arguments focus on the purification of worship and the prevention of tawhid distortion within modern social contexts. This study concludes that Ibn Baz’s thought not only reinforces the Qur’anic message of purifying worship but also provides a relevant theological paradigm for addressing modern phenomena that may obscure the oneness of Allah.